Evaluation of vascular quality of life questionnaire in dialysis patients with peripheral arterial disease treated by low-density lipoprotein apheresis. Issue 1 (December 2016) - Nagai, Kojiro; Harada, Megumi; Yokota, Narushi; Okada, Daigo; Michiwaki, Hiroyuki; Hirose, Daisuke; Doi, Toshio; Minakuchi, Jun; Tsuchida, Kenji
Abstract Background Peripheral arterial disease (PAD) is a common complication in dialysis patients. Early diagnosis and treatment are recommended. Low-density lipoprotein apheresis (LDL-A) is a potential therapy to improve PAD. However, the mechanism has yet to be fully clarified due to lack of established quantitative methods to assess the therapeutic effects of LDL-A treatment. Improvement of skin perfusion pressure (SPP) or ankle brachial index (ABI) is a representative therapy goal, but clinical symptoms were not always consistent with the values of SPP/ABI. Vascular quality of life questionnaire (VascuQOL) was proposed as a disease-specific QOL score, getting validated recently. The possibility of VascuQOL to reflect the severity of PAD in dialysis patients and evaluate the therapeutic effects of LDL-A has yet to be elucidated. Methods This is an observational study. LDL-A treatment was performed in 32 dialysis patients with PAD. They were divided to critical limb ischemia (CLI) group (17 subjects) and non-CLI group (15 subjects) according to their clinical manifestations. We examined the relationship of PAD severity with SPP, ABI, VascuQOL, and lipid profile such as apoB/apoA-I ratio, malondialdehyde-modified LDL, and remnant-like particles cholesterol. Furthermore, we evaluated these parameters successively to find out a suitable therapeutic marker just after the first LDL-A, at tenth LDL-A, and 1 month after completion of LDL-A treatment. Results All of the lipid markers were higher in CLI patients, but not significantly different from those in the non-CLI group. They decreased significantly just after LDL-A, although no changes were observed 1 month after completion of LDL-A treatment. ABI was significantly different between the CLI and non-CLI groups, but did not improve by LDL-A treatment. By contrast, SPP was ameliorated significantly and the peak was at tenth LDL-A. Among VascuQOL domains, "Symptom" and "Emotional" domains were significantly different between the CLI and non-CLI groups. The average score of VascuQOL increased successively until 1 month after completion of LDL-A treatment. Conclusions Several domains of VascuQOL can reflect the severity of PAD in dialysis patients. VascuQOL was a useful marker to show the prolonged therapeutic effects of LDL-A treatment in dialysis patients with PAD, independent of SPP.